INSP-15. ITCC-P4: A sustainable platform of molecularly well-characterized PDX models of pediatric cancers for high throughputin vivo testing. (3rd June 2022) - Kool, Marcel; Federico, Aniello; Surdez, Didier; Gopisetty, Apurva; Saberi-Ansari, Elnaz; Saint-Charles, Alexandra; Iddir, Yasmine; Waterfall, Joshua; Wierzbinska, Justyna; Schlicker, Andreas; Bhalsankar, Jaydutt; Mack, Norman; et al.
Abstract: Thanks to state-of-the-art molecular profiling techniques we by now have a much better understanding of pediatric cancers and what is driving them. On the other hand, we have also realized that pediatric cancers are much more heterogeneous than previously thought. Many new types and subtypes of pediatric cancers have been identified with distinct molecular and clinical characteristics. However, for many if not most of these new types and subtypes there is no specific treatment available, yet. In order to develop specific treatment protocols and to increase survival rates for pediatric cancer patients further, both at diagnosis and relapse/metastasis, we need a large collection of well-characterized preclinical models representing all the different types and subtypes. These models can be used for preclinical drug testing to prioritize the pediatric development of anticancer drugs that would be best targeting pediatric tumor biology. The ITCC-P4 consortium, which is a collaboration between many academic centers across Europe, several companies involved in in vivo preclinical testing, and ten pharmaceutical companies, started in 2017 with the overall aim to establish a sustainable platform of >400 molecularly well-characterized PDX models of high-risk pediatric cancers and to use them for in vivo testing of novel mechanism-of-action based treatments. Currently, 340 models have been fully established, including 87 brain tumor models and 253 non-brain tumor models, together representing many different tumor types both from primary and relapsed/metastatic disease. Out of these 340 models, 252 have been fully molecularly characterized, most of them together with their matching original tumors, and almost of all these models are currently being subjected to in vivo testing using three standard of care drugs and six novel mechanism-of-action based drugs. In this presentation, an update on the current status of the ITCC-P4 platform and the data we collectively have generated thus far will be presented.